Efficient biological fermentation catalyst and preparation method thereof
The biofermentation catalyst, with immobilized xylanase and β-glucosidase on a modified silica carrier, enhances the fermentation of traditional Chinese medicine, improving the extraction of effective ingredients and reducing toxicity.
Patent Information
- Application Number
- CN202411551317.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for biological fermentation of traditional Chinese medicine using microorganisms are inefficient and do not effectively enhance the dissolution of effective ingredients, leading to suboptimal extraction results.
A biofermentation catalyst is prepared by immobilizing xylanase and β-glucosidase on a modified silica carrier, which is created through a multi-step process involving polyacrylamide, bisphenol A epoxy resin, and polyethylene glycol, with metal ions like zinc and palladium, and modified with silane coupling agents and triethylamine to enhance enzyme stability and catalytic efficiency.
The biofermentation catalyst significantly improves the fermentation of traditional Chinese medicine, increasing the content of effective substances like baicalin and baicalein, while reducing toxicity and minimizing side reactions.
Smart Images

Figure BDA0005115155940000121 
Figure BDA0005115155940000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biological fermentation, and particularly relates to an efficient biological fermentation catalyst and a preparation method thereof. Background Art
[0002] Enzyme immobilization is a key technology in biotechnology and biocatalysis. Immobilized enzymes offer the following advantages: They can catalyze reactions without the use of hazardous solvents, contributing to green chemistry and sustainable production processes. Immobilization protects enzymes from harsh conditions such as high temperatures, extreme pH values, or mechanical shear, thereby improving their thermal and pH stability. Immobilized enzymes exhibit higher catalytic efficiency, with higher enzyme concentrations on the immobilized support, facilitating access to substrates. Furthermore, different enzymes can be immobilized on the same support, enabling synergistic catalysis across multiple enzyme systems and accelerating the reaction process.
[0003] Based on the advantages of immobilized enzymes, research on immobilized enzymes has increased in recent years. Patent CN118178524A discloses a dehydrogenation transaminase composition, preparation method, and application thereof. In the preparation process of the dehydrogenation transaminase composition, the patent uses an immobilized enzyme for pre-enzymatic hydrolysis to improve the dissolution of the active ingredient. Patent CN 117106764 A discloses an immobilized complex enzyme for preparing ultra-low molecular weight Dendrobium officinale polysaccharides, as well as its preparation method and application. The application uses γ-cyclodextrin to prepare a high-temperature resistant immobilized enzyme carrier material, and mixes different ratios of Aspergillus niger acid β-mannanase and cellulase. At the same time, the product enzyme obtained by fermentation of anaerobic Bacillus nubifolia and neutral protease are multi-compounded and immobilized on the aforementioned carrier material to obtain an immobilized complex enzyme. The immobilized complex enzyme can increase the yield of ultra-low molecular weight Dendrobium officinale polysaccharides.
[0004] However, there are few studies on immobilized enzyme catalysts related to traditional Chinese medicine fermentation. In recent years, the extraction of effective ingredients of traditional Chinese medicine is not limited to the previous solvent extraction method. There are more and more studies on the biological fermentation extraction of traditional Chinese medicine, but the effect of using only microorganisms to ferment traditional Chinese medicine is not ideal.
[0005] Therefore, developing a microorganism that can cooperate with microorganisms to efficiently catalyze the decomposition of traditional Chinese medicine and improve the dissolution of effective ingredients is of great significance to the biological fermentation of traditional Chinese medicine. Summary of the Invention
[0006] The invention discloses an efficient biofermentation catalyst and a preparation method thereof. The prepared biofermentation catalyst can achieve efficient catalytic effect under relatively mild conditions, can significantly improve the fermentation effect of microorganisms on traditional Chinese medicine, reduce the toxicity of traditional Chinese medicine, and increase the content of effective substances.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] The first aspect of the present invention provides a method for preparing an efficient biofermentation catalyst, comprising the following preparation steps:
[0009] (1) After polyacrylamide, bisphenol A epoxy resin and polyethylene glycol are uniformly mixed, a curing agent is added and mixed uniformly, and the mixture is cured at 75-85° C. for 2-3 hours. The obtained solid is washed with deionized water until neutral, and dried under vacuum to obtain a polymer template;
[0010] (2) After completely immersing the polymer template of step (1) in tetraethyl orthosilicate for 2.5-3.5 hours, fumigating with ammonia at 30-35°C for 10-12 hours, taking out the composite and drying it at 60-70°C for 1.5-2.5 hours, and then heating and calcining it at a rate of 10-15°C / min to obtain a silica carrier;
[0011] (3) soaking the silica support of step (2) in a functional solution for 2-3 hours, then taking it out and drying it at 90-100° C. for 1-2 hours, calcining it at 200-300° C. for 1-1.5 hours, then heating it to 600-650° C. and calcining it for 20-30 minutes, and then immersing an equal volume of the obtained solid 1 in a zinc-palladium mixed solution for 5-6 hours, hydrothermally reacting it in a closed container at 90-100° C. for 16-20 hours, cooling, washing, and drying to obtain a specific support;
[0012] (4) The specific carrier of step (3) is modified with a silane coupling agent, and the modified specific carrier is dispersed in methanol, acrylic acid is added dropwise thereto at 0-4°C, and the reaction is carried out at 20-30°C for 20-24 hours, and the obtained solid 2 is separated, washed, and dried. The solid 2 is dispersed in methanol, triethylamine is added dropwise thereto at 0-4°C, and the reaction is carried out at 20-30°C for 20-24 hours, and the solid 2 is separated, washed, and dried to obtain the modified specific carrier;
[0013] (5) Immersing an equal volume of the modified specific carrier obtained in step (4) in a mixed enzyme solution at 10-15° C. for 6-10 hours, separating and washing to obtain a biofermentation catalyst.
[0014] In some embodiments, the polyacrylamide in step (1) is a nonionic polyacrylamide with a number average molecular weight of 2 million to 14 million, the number average molecular weight of the bisphenol A epoxy resin is 700 to 1500, and the number average molecular weight of the polyethylene glycol is 1000 to 2000.
[0015] In some embodiments, the mass ratio of the polyacrylamide, bisphenol A epoxy resin and polyethylene glycol is (6-8):(3.5-4.5):1.
[0016] Preferably, the mass ratio of the polyacrylamide, bisphenol A epoxy resin and polyethylene glycol is 7:4:1.
[0017] In some embodiments, the temperature is raised to 700-750° C. and the calcination time is 2-4 hours.
[0018] Preferably, the temperature is raised to 725° C. and the calcination time is 3 hours.
[0019] In some embodiments, the functional solution of step (3) is composed of polyethylene glycol with a number average molecular weight of 400-800 and Zn(Ac)2·2H2O dissolved in deionized water; the concentrations of polyethylene glycol and Zn(Ac)2·2H2O in the functional solution are 8-12 wt% and 0.5-1 mol / L, respectively.
[0020] Preferably, the concentrations of polyethylene glycol and Zn(Ac)2·2H2O in the functional solution are 10 wt% and 0.75 mol / L, respectively.
[0021] In some embodiments, the concentrations of zinc ions and palladium ions in the zinc-palladium mixed solution of step (3) are 0.8-1 mol / L and 0.02-0.05 mol / L, respectively.
[0022] Preferably, the concentrations of zinc ions and palladium ions in the zinc-palladium mixed solution in step (3) are 0.9 mol / L and 0.035 mol / L, respectively.
[0023] In some embodiments, in step (4), the mass ratio of the specific carrier to acrylic acid is (1-2):1; the mass ratio of the solid 2 to triethylamine is 1:(0.8-0.9).
[0024] Preferably, in step (4), the mass ratio of the specific carrier to acrylic acid is 1.5:1; and the mass ratio of the solid 2 to triethylamine is 1:0.85.
[0025] In some embodiments, the mixed enzyme solution in step (5) is obtained by dispersing xylanase and β-glucosidase in deionized water; the concentrations of xylanase and β-glucosidase in the mixed enzyme solution are 1-4 wt% and 0.5-1 wt%, respectively.
[0026] In some embodiments, the mass ratio of the xylanase to the β-glucosidase is (4-6):1.
[0027] Preferably, the mass ratio of the xylanase to the β-glucosidase is 5:1.
[0028] The second aspect of the present invention provides a biofermentation catalyst prepared according to the preparation method described above.
[0029] The present invention loads two functional enzymes on a specific carrier, and the functional enzymes can act together with the metal ions in the carrier to improve the catalytic effect of the catalyst on the biological fermentation of traditional Chinese medicine.
[0030] The invention uses polyacrylamide, bisphenol A epoxy resin and polyethylene glycol as raw materials to prepare a polymer template, and the polymer template has excellent biocompatibility, mechanical strength and stability. The pore structure, pore size distribution, and hydrophilicity of the polymer template are regulated by controlling the ratio of raw materials, which is beneficial for the subsequent formation of the carrier. The polymer template is then immersed in a tetraethyl orthosilicate solution, where the tetraethyl orthosilicate is hydrolyzed and condensed to form silanols. These silanols form a three-dimensional silica network through polymerization reaction. The silica carrier is then calcined to obtain a silica carrier with a macroporous structure and a high specific surface area, which is beneficial for improving the transmission efficiency of the catalyst and the progress of the catalytic reaction. The silica carrier is then immersed in a functional solution and calcined. The internal structure of the obtained solid 1 has protrusions, which increase adsorption sites and are beneficial for the subsequent attachment of metal ions and enzymes. A certain amount of zinc and palladium metal ions are then loaded on the solid 1. On the one hand, the two metals themselves also have certain catalytic effects. On the other hand, their charge, roughness, and chemical composition may affect the adsorption, stability, and interaction of the two enzymes by providing a specific chemical environment or electronic properties, thereby affecting their catalytic activity. In addition, the present invention also modifies the specific carrier by using a coupling agent, acrylic acid, and triethylamine to improve the adhesion, stability, and catalytic effect of the enzyme on the carrier.
[0031] The applicant discovered that by immobilizing xylanase and β-glucosidase on a modified specific carrier, the two have high stability and complementary catalytic activities, reducing the generation of unnecessary side reactions and by-products and improving catalytic efficiency. This is because, on the one hand, immobilizing the two enzymes on the same carrier or through a specific spatial arrangement can optimize their synergistic effect, achieving closer physical proximity and more efficient substrate channels; on the other hand, xylanase is mainly responsible for hydrolyzing the β-1,4-glycosidic bonds of xylans in various traditional Chinese medicines to produce oligoxylose and xylose, while β-glucosidase can further hydrolyze these oligoxylose, improving the dissolution of active ingredients. The synergistic effect of these two enzymes can more effectively degrade xylan completely. Moreover, the activity of one enzyme may be activated by the activity product of the other enzyme, thereby improving the efficiency of the entire catalytic process.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention loads two functional enzymes on a specific carrier. The functional enzymes can work together with the metal ions in the carrier to improve the catalytic effect of the catalyst on the biological fermentation of traditional Chinese medicine. The biological fermentation catalyst can have a high-efficiency catalytic effect under relatively mild conditions, significantly improve the fermentation effect of microorganisms on traditional Chinese medicine, reduce the toxicity of traditional Chinese medicine, and increase the content of effective substances.
[0034] 2. The present invention prepares a modified specific carrier with a specific internal structure and attachment sites, which can improve the adhesion, stability and catalytic effect of the enzyme on the carrier.
[0035] 3. The present invention immobilizes xylanase and β-glucosidase on a modified specific carrier. The two have high stability and complementary catalytic activities, which reduces unnecessary side reactions and the generation of by-products and improves catalytic efficiency. DETAILED DESCRIPTION
[0036] Various exemplary embodiments of the present invention are now described in detail. This detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing particular embodiments and are not intended to limit the present invention. In addition, for the numerical ranges in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value within any stated value or stated range and any other stated value or intermediate value within the range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may be used in the practice or testing of the present invention. Various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention, as will be apparent to those skilled in the art. Other embodiments obtained from the present invention description will be apparent to those skilled in the art. This application description and examples are exemplary only.
[0038] The terms “include,” “including,” “have,” or “contain” used in this document are open-ended terms, meaning including but not limited to.
[0039] The mass fractions described in the following embodiments may be grams, kilograms, tons or other mass units.
[0040] The polyacrylamide used in the present invention is a nonionic polyacrylamide with a number average molecular weight of 10 million; the number average molecular weight of the polyethylene glycol used in the polymer template is 1000, and the number average molecular weight of the polyethylene glycol used in the functional solution is 600; the epoxy equivalent of the bisphenol A epoxy resin used is 475-550 and is purchased from Guangzhou Zhuocen Chemical Co., Ltd.; the curing agent used is diethylenetriamine; the enzymatic activity of the xylanase used is 80,000 u / g; the enzymatic activity of the beta-glucosidase used is 80,000 u / g; and the silane coupling agent used is KH550.
[0041] Preparation Example 1
[0042] Preparation of functional solution:
[0043] Take 10 g of polyethylene glycol and 0.75 mol of Zn(Ac)2·2H2O and dissolve them in 100 mL of deionized water to obtain a functional solution.
[0044] Preparation Example 2
[0045] Preparation of functional solution:
[0046] 7 g of polyethylene glycol and 0.75 mol of Zn(Ac)2·2H2O were dissolved in 100 mL of deionized water to obtain a functional solution.
[0047] Preparation Example 3
[0048] Preparation of functional solution:
[0049] Take 0.75 mol Zn(Ac)2·2H2O and dissolve it in 100 mL deionized water to obtain a functional solution.
[0050] Preparation Example 4
[0051] Preparation of zinc-palladium mixture:
[0052] Take 0.9 mol zinc chloride and 0.035 mol palladium chloride and dissolve them in 1 L of deionized water to obtain a zinc-palladium mixed solution.
[0053] Preparation Example 5
[0054] Preparation of zinc-palladium mixture:
[0055] Take 0.7 mol zinc chloride and 0.035 mol palladium chloride and dissolve them in 1 L of deionized water to obtain a zinc-palladium mixed solution.
[0056] Preparation Example 6
[0057] Preparation of zinc-palladium mixture:
[0058] Take 0.9 mol zinc chloride and 0.01 mol palladium chloride and dissolve them in 1 L of deionized water to obtain a zinc-palladium mixed solution.
[0059] Preparation Example 7
[0060] Preparation of mixed enzyme solution:
[0061] 3 g of xylanase and 0.6 g of β-glucosidase were respectively dispersed in 100 mL of deionized water to obtain a mixed enzyme solution.
[0062] Preparation Example 8
[0063] Preparation of mixed enzyme solution:
[0064] 3 g of xylanase and 1 g of β-glucosidase were respectively dispersed in 100 mL of deionized water to obtain a mixed enzyme solution.
[0065] Preparation Example 9
[0066] Preparation of mixed enzyme solution:
[0067] 3 g of xylanase and 0.4 g of β-glucosidase were respectively dispersed in 100 mL of deionized water to obtain a mixed enzyme solution.
[0068] Example 1
[0069] A method for preparing an efficient biofermentation catalyst comprises the following steps:
[0070] (1) After 70 g of polyacrylamide, 40 g of bisphenol A epoxy resin, and 10 g of polyethylene glycol were mixed evenly, 10 g of curing agent was added and mixed evenly, and the mixture was cured at 80° C. for 2.5 h. The obtained solid was washed with deionized water until neutral, and dried under vacuum to constant weight to obtain a polymer template;
[0071] (2) The polymer template of step (1) was completely immersed in tetraethyl orthosilicate for 2.5 hours, and then fumigated with ammonia at 30°C in an ammonia atmosphere for 10 hours. The composite was taken out and dried at 65°C for 2 hours, and then heated to 725°C at a rate of 12.5°C / min and calcined for 3 hours to obtain a silica carrier;
[0072] (3) Soaking the silica support of step (2) in the functional solution for 2 hours, then taking it out and drying it at 90°C for 2 hours, calcining it at 250°C for 1.25 hours, then heating it to 625°C and calcining it for 25 minutes, and immersing an equal volume of the obtained solid 1 in a zinc-palladium mixed solution for 5 hours, hydrothermally reacting it at 90°C in a sealed container for 20 hours, cooling it to room temperature, washing it with deionized water three times, and drying it at 60°C to constant weight to obtain a specific support;
[0073] (4) 50 g of the specific carrier of step (3) was placed in 250 mL of methanol, and 50 g of silane coupling agent was added thereto. After modification at 35 ° C and a stirring speed of 150 r / min for 6 h, the mixture was washed with methanol three times, vacuum filtered, and dried at 60 ° C to constant weight to obtain a modified specific carrier. 50 g of the modified specific carrier was dispersed in 500 mL of methanol, 33.3 g of acrylic acid was added dropwise thereto at 0 ° C, and the mixture was reacted at 25 ° C for 22 h. The mixture was separated, washed with methanol three times, and dried at 60 ° C to constant weight to obtain solid 2. 60 g of solid 2 was dispersed in 800 mL of methanol, 51 g of triethylamine was added dropwise thereto at 0 ° C, and the mixture was reacted at 25 ° C for 22 h. The mixture was separated, washed with methanol three times, and dried at 60 ° C to constant weight to obtain a modified specific carrier;
[0074] (5) Immersing an equal volume of the modified specific carrier obtained in step (4) in the mixed enzyme solution, soaking at 10° C. for 8 h, separating, and washing with deionized water three times to obtain a biofermentation catalyst.
[0075] The functional solution used was obtained from Preparation Example 1; the zinc-palladium mixed solution used was obtained from Preparation Example 4; and the mixed enzyme solution used was obtained from Preparation Example 7.
[0076] Example 2
[0077] A method for preparing an efficient biofermentation catalyst comprises the following steps:
[0078] (1) After uniformly mixing 60 g of polyacrylamide, 35 g of bisphenol A epoxy resin, and 10 g of polyethylene glycol, 8.75 g of a curing agent was added and mixed uniformly. The mixture was cured at 85° C. for 2 h. The obtained solid was washed with deionized water until neutral, and dried under vacuum to constant weight to obtain a polymer template.
[0079] (2) After the polymer template of step (1) is completely immersed in tetraethyl orthosilicate for 3.5 hours, it is fumigated with ammonia at 35°C in an ammonia atmosphere for 12 hours, the composite is taken out and dried at 70°C for 1.5 hours, and then heated to 750°C at a rate of 10°C / min and calcined for 2 hours to obtain a silica carrier;
[0080] (3) Soaking the silica support of step (2) in the functional solution for 3 hours, then taking it out and drying it at 100°C for 1 hour, calcining it at 200°C for 1.5 hours, and then heating it to 600°C for calcining for 30 minutes. An equal volume of the obtained solid 1 was immersed in a zinc-palladium mixed solution for 6 hours, and hydrothermally reacted at 100°C in a sealed container for 16 hours. The solid was cooled to room temperature, washed with deionized water 3 times, and dried at 60°C to constant weight to obtain a specific support;
[0081] (4) 50 g of the specific carrier of step (3) was placed in 250 mL of methanol, and 50 g of silane coupling agent was added thereto. After modification at 35 ° C and a stirring speed of 150 r / min for 6 h, the mixture was washed with methanol three times, vacuum filtered, and dried at 60 ° C to constant weight to obtain a modified specific carrier. 50 g of the modified specific carrier was dispersed in 500 mL of methanol, 50 g of acrylic acid was added dropwise thereto at 0 ° C, and the mixture was reacted at 20 ° C for 24 h. The mixture was separated, washed with methanol three times, and dried at 60 ° C to constant weight to obtain solid 2. 60 g of solid 2 was dispersed in 800 mL of methanol, 48 g of triethylamine was added dropwise thereto at 0 ° C, and the mixture was reacted at 20 ° C for 24 h. The mixture was separated, washed with methanol three times, and dried at 60 ° C to constant weight to obtain a modified specific carrier;
[0082] (5) Immersing an equal volume of the modified specific carrier obtained in step (4) in the mixed enzyme solution, soaking the mixture at 10° C. for 10 h, separating the mixture, and washing the mixture with deionized water three times to obtain a biofermentation catalyst.
[0083] The functional solution used was obtained from Preparation Example 1; the zinc-palladium mixed solution used was obtained from Preparation Example 4; and the mixed enzyme solution used was obtained from Preparation Example 7.
[0084] Example 3
[0085] A method for preparing an efficient biofermentation catalyst comprises the following steps:
[0086] (1) 80 g of polyacrylamide, 45 g of bisphenol A epoxy resin, and 10 g of polyethylene glycol were mixed uniformly, and then 11.25 g of curing agent was added and mixed uniformly. The mixture was cured at 85° C. for 2 h. The obtained solid was washed with deionized water until neutral, and dried under vacuum to constant weight to obtain a polymer template.
[0087] (2) After the polymer template of step (1) is completely immersed in tetraethyl orthosilicate for 3.5 hours, it is fumigated with ammonia at 35°C in an ammonia atmosphere for 10 hours, the composite is taken out and dried at 70°C for 1.5 hours, and then heated to 700°C at a rate of 15°C / min and calcined for 4 hours to obtain a silica carrier;
[0088] (3) Soaking the silica support of step (2) in the functional solution for 3 hours, then taking it out and drying it at 90°C for 2 hours, calcining it at 300°C for 1 hour, and then heating it to 650°C for calcining it for 20 minutes. An equal volume of the obtained solid 1 was immersed in a zinc-palladium mixed solution for 6 hours, and hydrothermally reacted at 90°C in a sealed container for 20 hours. The solid was cooled to room temperature, washed with deionized water 3 times, and dried at 60°C to constant weight to obtain a specific support;
[0089] (4) 50 g of the specific carrier of step (3) was placed in 250 mL of methanol, and 50 g of silane coupling agent was added thereto. After modification at 35 ° C and a stirring speed of 150 r / min for 6 h, the mixture was washed with methanol three times, vacuum filtered, and dried at 60 ° C to constant weight to obtain a modified specific carrier. 50 g of the modified specific carrier was dispersed in 500 mL of methanol, 25 g of acrylic acid was added dropwise thereto at 4 ° C, and the mixture was reacted at 30 ° C for 20 h. The mixture was separated, washed with methanol three times, and dried at 60 ° C to constant weight to obtain solid 2. 60 g of solid 2 was dispersed in 800 mL of methanol, 54 g of triethylamine was added dropwise thereto at 4 ° C, and the mixture was reacted at 30 ° C for 20 h. The mixture was separated, washed with methanol three times, and dried at 60 ° C to constant weight to obtain a modified specific carrier;
[0090] (5) Immersing an equal volume of the modified specific carrier obtained in step (4) in the mixed enzyme solution, soaking at 15° C. for 6 h, separating, and washing with deionized water three times to obtain a biofermentation catalyst.
[0091] The functional solution used was obtained from Preparation Example 1; the zinc-palladium mixed solution used was obtained from Preparation Example 4; and the mixed enzyme solution used was obtained from Preparation Example 7.
[0092] Example 4
[0093] A method for preparing an efficient biofermentation catalyst, the specific implementation method is the same as that of Example 1, except that the functional solution used is obtained from Preparation Example 2.
[0094] Example 5
[0095] A method for preparing an efficient biofermentation catalyst, the specific implementation method is the same as that of Example 1, except that the functional solution used is obtained from Preparation Example 3.
[0096] Example 6
[0097] A method for preparing an efficient biofermentation catalyst, the specific implementation method is the same as that of Example 1, except that the zinc-palladium mixed solution used is obtained from Preparation Example 5.
[0098] Example 7
[0099] A method for preparing an efficient biofermentation catalyst, the specific implementation method is the same as that of Example 1, except that the zinc-palladium mixed solution used is obtained from Preparation Example 6.
[0100] Example 8
[0101] A method for preparing an efficient biofermentation catalyst, the specific implementation method is the same as that of Example 1, except that the mixed enzyme solution used is obtained from Preparation Example 8.
[0102] Example 9
[0103] A method for preparing an efficient biofermentation catalyst, the specific implementation method is the same as that of Example 1, except that the mixed enzyme solution used is obtained from Preparation Example 9.
[0104] Comparative Example 1
[0105] A method for preparing an efficient biofermentation catalyst comprises the following steps:
[0106] (1) After 70 g of polyacrylamide, 40 g of bisphenol A epoxy resin, and 10 g of polyethylene glycol were mixed evenly, 10 g of curing agent was added and mixed evenly, and the mixture was cured at 80° C. for 2.5 h. The obtained solid was washed with deionized water until neutral, and dried under vacuum to constant weight to obtain a polymer template;
[0107] (2) The polymer template of step (1) was completely immersed in tetraethyl orthosilicate for 2.5 hours, and then fumigated with ammonia at 30°C for 10 hours. The composite was taken out and dried at 65°C for 2 hours, and then heated to 725°C at a rate of 12.5°C / min and calcined for 2.5 hours to obtain a silica carrier;
[0108] (3) 50 g of the silica carrier of step (2) was placed in 250 mL of methanol, and 50 g of silane coupling agent was added thereto. After modification at 35 ° C. and a stirring speed of 150 r / min for 6 h, the mixture was washed three times with methanol, vacuum filtered, and dried at 60 ° C to constant weight to obtain a modified silica carrier. 50 g of the modified specific carrier was dispersed in 500 mL of methanol, 33.3 g of acrylic acid was added dropwise thereto at 0 ° C., the mixture was reacted at 25 ° C. for 22 h, separated, washed with methanol three times, and dried at 60 ° C. to obtain a solid 2. 60 g of solid 2 was dispersed in 800 mL of methanol, 51 g of triethylamine was added dropwise thereto at 0 ° C., the mixture was reacted at 25 ° C. for 22 h, separated, washed with methanol three times, and dried at 60 ° C. to obtain a modified silica carrier;
[0109] (4) Immersing an equal volume of the modified silica support prepared in step (3) in the mixed enzyme solution at 10° C. for 8 h, separating, and washing with deionized water three times to obtain a biofermentation catalyst.
[0110] The mixed enzyme solution used was obtained from Preparation Example 7.
[0111] Comparative Example 2
[0112] A method for preparing an efficient biofermentation catalyst comprises the following steps:
[0113] (1) After 70 g of polyacrylamide, 40 g of bisphenol A epoxy resin, and 10 g of polyethylene glycol were mixed evenly, 10 g of curing agent was added and mixed evenly, and the mixture was cured at 80° C. for 2.5 h. The obtained solid was washed with deionized water until neutral, and dried under vacuum to constant weight to obtain a polymer template;
[0114] (2) After the polymer template of step (1) is completely immersed in tetraethyl orthosilicate for 2.5 hours, it is fumigated with ammonia at 30°C for 10 hours, the composite is taken out and dried at 65°C for 2 hours, and then heated to 725°C at a rate of 12.5°C / min and calcined for 2.5 hours to obtain a silica carrier;
[0115] (3) Soaking the silica support prepared in step (2) in the functional solution for 2 h, then taking it out and drying it at 90° C. for 2 h, calcining it at 250° C. for 1.25 h, and then heating it to 625° C. and calcining it for 25 min to obtain a specific support;
[0116] (4) 50 g of the specific carrier of step (3) was placed in 250 mL of methanol, and 50 g of silane coupling agent was added thereto. After modification at 35 ° C and a stirring speed of 150 r / min for 6 h, the mixture was washed with methanol three times, vacuum filtered, and dried at 60 ° C to constant weight to obtain a modified specific carrier. 50 g of the modified specific carrier was dispersed in 500 mL of methanol, 33.3 g of acrylic acid was added dropwise thereto at 0 ° C, and the mixture was reacted at 25 ° C for 22 h. The mixture was separated, washed with methanol three times, and dried at 60 ° C to constant weight to obtain solid 2. 60 g of solid 2 was dispersed in 800 mL of methanol, 51 g of triethylamine was added dropwise thereto at 0 ° C, and the mixture was reacted at 25 ° C for 22 h. The mixture was separated, washed with methanol three times, and dried at 60 ° C to constant weight to obtain a modified specific carrier;
[0117] (5) Immersing an equal volume of the modified specific carrier obtained in step (4) in the mixed enzyme solution, soaking at 10° C. for 8 h, separating, and washing with deionized water three times to obtain a biofermentation catalyst.
[0118] The functional solution used was obtained from Preparation Example 1; the mixed enzyme solution used was obtained from Preparation Example 7.
[0119] Comparative Example 3
[0120] A method for preparing an efficient biofermentation catalyst comprises the following steps:
[0121] (1) After 70 g of polyacrylamide, 40 g of bisphenol A epoxy resin, and 10 g of polyethylene glycol were mixed evenly, 10 g of curing agent was added and mixed evenly, and the mixture was cured at 80° C. for 2.5 h. The obtained solid was washed with deionized water until neutral, and dried under vacuum to constant weight to obtain a polymer template;
[0122] (2) The polymer template of step (1) was completely immersed in tetraethyl orthosilicate for 2.5 hours, and then fumigated with ammonia at 30°C for 10 hours. The composite was taken out and dried at 65°C for 2 hours, and then heated to 725°C at a rate of 12.5°C / min and calcined for 2.5 hours to obtain a silica carrier;
[0123] (3) Soaking the silica support of step (2) in the functional solution for 2 hours, then taking it out and drying it at 90°C for 2 hours, calcining it at 250°C for 1.25 hours, then heating it to 625°C and calcining it for 25 minutes, and immersing an equal volume of the obtained solid 1 in a zinc-palladium mixed solution for 5 hours, hydrothermally reacting it at 90°C in a sealed container for 20 hours, cooling it to room temperature, washing it with deionized water three times, and drying it at 60°C to constant weight to obtain a specific support;
[0124] (4) 50 g of the specific carrier of step (3) was dispersed in 500 mL of methanol, 33.3 g of acrylic acid was added dropwise thereto at 0°C, and the mixture was reacted at 25°C for 22 h, separated, washed with methanol three times, and dried at 60°C to constant weight to obtain solid 2. 60 g of solid 2 was dispersed in 800 mL of methanol, 51 g of triethylamine was added dropwise thereto at 0°C, and the mixture was reacted at 25°C for 22 h, separated, washed with methanol three times, and dried at 60°C to constant weight to obtain a modified specific carrier;
[0125] (5) Immersing an equal volume of the modified specific carrier obtained in step (4) in the mixed enzyme solution, soaking at 10° C. for 8 h, separating, and washing with deionized water three times to obtain a biofermentation catalyst.
[0126] The functional solution used was obtained from Preparation Example 1; the zinc-palladium mixed solution used was obtained from Preparation Example 4; and the mixed enzyme solution used was obtained from Preparation Example 7.
[0127] Comparative Example 4
[0128] A method for preparing an efficient biofermentation catalyst comprises the following steps:
[0129] (1) After 70 g of polyacrylamide, 40 g of bisphenol A epoxy resin, and 10 g of polyethylene glycol were mixed evenly, 10 g of curing agent was added and mixed evenly, and the mixture was cured at 80° C. for 2.5 h. The obtained solid was washed with deionized water until neutral, and dried under vacuum to constant weight to obtain a polymer template;
[0130] (2) The polymer template of step (1) was completely immersed in tetraethyl orthosilicate for 2.5 hours, and then fumigated with ammonia at 30°C for 10 hours. The composite was taken out and dried at 65°C for 2 hours, and then heated to 725°C at a rate of 12.5°C / min and calcined for 2.5 hours to obtain a silica carrier;
[0131] (3) Soaking the silica support of step (2) in the functional solution for 2 hours, then taking it out and drying it at 90°C for 2 hours, calcining it at 250°C for 1.25 hours, then heating it to 625°C and calcining it for 25 minutes, and immersing an equal volume of the obtained solid 1 in a zinc-palladium mixed solution for 5 hours, hydrothermally reacting it at 90°C in a sealed container for 20 hours, cooling it to room temperature, washing it with deionized water three times, and drying it at 60°C to constant weight to obtain a specific support;
[0132] (4) Immersing an equal volume of the specific carrier prepared in step (3) in the mixed enzyme solution, soaking at 10° C. for 8 h, separating, and washing with deionized water three times to obtain a biofermentation catalyst.
[0133] The functional solution used was obtained from Preparation Example 1; the zinc-palladium mixed solution used was obtained from Preparation Example 4; and the mixed enzyme solution used was obtained from Preparation Example 7.
[0134] Performance testing of biofermentation catalysts
[0135] Fermentation experiment The bio-fermentation catalysts obtained in each embodiment and comparative example were subjected to the following fermentation experiments:
[0136] Experimental group: 500 g of dried, crushed Scutellaria baicalensis root that had passed a 60-mesh sieve were added with 70 wt% pure water, 1.5 wt% of a biofermentation catalyst (the biofermentation catalyst obtained in each Example and Comparative Example), and 7.5 wt% of a mixed bacterial culture solution. The pH was adjusted to 6, and the mixture was fermented in an aerobic environment at 25°C for 6 days to obtain a Scutellaria baicalensis fermentation product. Twice the weight of pure water was then added to the fermentation product, and the mixture was soaked for 6 hours. The mixture was filtered to obtain a Scutellaria baicalensis fermentation product extract.
[0137] The total concentration of the mixed bacterial culture solution used was 5×10 7 CFU / mL, including Pleurotus ostreatus CICC 14083, Trichoderma reesei CICC 13052, and Bacillus subtilis CICC 10275 in a quantity ratio of 2.5:1.5:1.
[0138] Blank control group: No biological fermentation catalyst was added, and other conditions were the same as those of the experimental group.
[0139] Control group: xylanase and β-glucosidase of equal mass and mass ratio of 5:1 were used instead of the biological fermentation catalyst, and other conditions were the same as those of the experimental group.
[0140] The baicalin content and baicalein content in the scutellaria baicalensis fermentation extract obtained by fermentation using the biological fermentation catalyst of each embodiment and comparative example were analyzed. The specific analysis method refers to Chapter 2, Section 2.2.1.4 of "Preparation of Scutellaria baicalensis Extract Fermented by Lactobacillus salivarius and Observation of Its Efficacy on Mycoplasma Gallisepticum Infection".
[0141] The specific test results are shown in Table 1.
[0142] Table 1
[0143]
[0144]
[0145] As shown in Table 1, the biofermentation catalysts prepared in Examples 1-3 have a good catalytic effect, and can promote the fermentation of Scutellaria baicalensis by the mixed flora better than the blank control group and the control group, and significantly increase the baicalin content and baicalein content in the Scutellaria baicalensis fermentation extract.
[0146] Compared with Example 1, the concentration and composition of the functional solutions used in Examples 4 and 5 changed, which reduced the adsorption sites inside the silica carrier, which was not conducive to the attachment of catalytic metal ions and enzymes, resulting in a decrease in the catalytic performance of the catalyst; the ratio of zinc to palladium in the zinc-palladium mixed solution used in Examples 6 and 7 changed, which changed the catalytic performance of the two and their effects on the functional enzymes, resulting in a decrease in the catalytic performance of the catalyst; the ratio of xylanase and β-glucosidase in the mixed enzyme solution used in Examples 8 and 9 changed, which reduced the synergistic catalytic effect of the two, resulting in a decrease in the catalytic performance of the catalyst, and the baicalin content and baicalein content in the Scutellaria baicalensis fermentation extract were also reduced.
[0147] Compared with Example 1, in Comparative Example 1, the carrier was not modified by the functional solution and the zinc-palladium mixture, in Comparative Example 2, the carrier was not modified by the zinc-palladium mixture, in Comparative Example 3, the carrier was not modified by the coupling agent, and in Comparative Example 4, the specific carrier was not modified. All of these results in a decrease in the catalytic effect of the biofermentation catalyst, and the baicalin content and baicalein content in the Scutellaria baicalensis fermentation extract are also reduced.
[0148] The above is only a preferred embodiment of the present invention and does not limit the present application in any form. Although the present application is disclosed as above with a preferred embodiment, it is not intended to limit the present application. Any technician familiar with this profession, without departing from the scope of the technical solution of the present application, makes some changes or modifications using the technical content disclosed above, which are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.
Claims
1. A method for preparing an efficient biofermentation catalyst, characterized in that: The method comprises the following preparation steps: (1) After polyacrylamide, bisphenol A epoxy resin and polyethylene glycol are uniformly mixed, a curing agent is added and mixed uniformly, and the mixture is cured at 75-85° C. for 2-3 hours. The obtained solid is washed with deionized water until it is neutral, and dried under vacuum to obtain a polymer template; (2) After the polymer template of step (1) is completely immersed in tetraethyl orthosilicate for 2.5-3.5 hours, it is fumigated with ammonia at 30-35° C. for 10-12 hours, the composite is taken out and dried at 60-70° C. for 1.5-2.5 hours, and then heated and calcined at a rate of 10-15° C. / min to obtain a silica carrier; (3) soaking the silica carrier of step (2) in the functional solution for 2-3 hours, then taking it out and drying it at 90-100° C. for 1-2 hours, calcining it at 200-300° C. for 1-1.5 hours, then heating it to 600-650° C. for calcining it for 20-30 minutes, and then immersing an equal volume of the obtained solid 1 in a zinc-palladium mixed solution for 5-6 hours, hydrothermally reacting it in a closed container at 90-100° C. for 16-20 hours, cooling, washing, and drying to obtain a specific carrier; (4) The specific carrier of step (3) is modified with a silane coupling agent, and the modified specific carrier is dispersed in methanol, acrylic acid is added dropwise at 0-4° C., and the reaction is carried out at 20-30° C. for 20-24 hours, and the solid 2 is separated, washed, and dried to obtain a solid 2, and the solid 2 is dispersed in methanol, triethylamine is added dropwise at 0-4° C., and the reaction is carried out at 20-30° C. for 20-24 hours, and the solid 2 is separated, washed, and dried to obtain a modified specific carrier; (5) Immersing an equal volume of the modified specific carrier of step (4) in the mixed enzyme solution at 10-15° C. for 6-10 hours, separating and washing to obtain a biofermentation catalyst.
2. The preparation method according to claim 1, characterized in that: In the step (1), the polyacrylamide is a nonionic polyacrylamide with a number average molecular weight of 2 million to 14 million, the number average molecular weight of the bisphenol A type epoxy resin is 700 to 1500, and the number average molecular weight of the polyethylene glycol is 1000 to 2000.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the polyacrylamide, bisphenol A epoxy resin and polyethylene glycol is (6-8):(3.5-4.5):
1.
4. The preparation method according to claim 1, characterized in that: The temperature is raised to 700-750° C. and the calcination time is 2-4 hours.
5. The preparation method according to claim 1, characterized in that: The functional solution of step (3) is composed of polyethylene glycol with a number average molecular weight of 400-800 and Zn(Ac)2·2H2O dissolved in deionized water; the concentrations of polyethylene glycol and Zn(Ac)2·2H2O in the functional solution are 8-12wt% and 0.5-1mol / L respectively.
6. The preparation method according to claim 1, characterized in that: The concentrations of zinc ions and palladium ions in the zinc-palladium mixed solution of step (3) are 0.8-1 mol / L and 0.02-0.05 mol / L respectively.
7. The preparation method according to claim 1, characterized in that: In the step (4), the mass ratio of the specific carrier to acrylic acid is (1-2):1; the mass ratio of the solid 2 to triethylamine is 1:(0.8-0.9).
8. The preparation method according to claim 1, characterized in that: In step (5), the mixed enzyme solution is obtained by dispersing xylanase and β-glucosidase in deionized water; the concentrations of xylanase and β-glucosidase in the mixed enzyme solution are 1-4wt% and 0.5-1wt%, respectively.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the xylanase to the β-glucosidase is (4-6):
1.
10. A biological fermentation catalyst prepared by the preparation method according to any one of claims 1 to 9.
